The Genogram Characteristic of Cleft Lip and/or Palate Cases in Aceh - Ibhaliswan, Andi Akbar; Budiman, B; Khairan, K; Amirsyah, Mirnasari; Ismy, Jufriady (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Objective: To describe the characteristic of genogram of CL/P cases in Aceh with sociodemographic features and maternal pregnancy history. Methods: cross sectional study with retrospective approach. Data of patients underwent CL/P surgery at the Yayasan Senyum Aceh from 2021-2023 were collected and family member interview was conducted via telephone. Results: 155 patients met our study criteria. Results showed that the majority of patients were male(56.1%), with left unilateral CLP type(43.2%), and live at an altitude of 0-500 meter-ASL(67.09%). Regarding family characteristics, data was obtained for each father and mother, the majority had a secondary education 47.1% and 49.7% respectively, Acehnese 78.7% and 80.6%, working 100% and 29%, with medium category household-income(32.9%), mothers were more than 25-35 years old (57.4%) age group and fathers were less than 40 years old(52.2%). For the pregnancy history:72.2% of mother aged 21-34 years old, 65.8% had less than 2 children, 96.8% had no comorbidities, 94.2% no history of trauma  and folic acid consumption during pregnancy. A family history found in 20% of all cases, with 11% was from 2nd generation. Left unilateral CLP was diagnosed in 1st generation (6.06%), 2nd generation (21.22%), and 3rd generation(18.18%). Conclusion: The characteristics of CL/P patients in Aceh were mostly: male, with left unilateral CLP type, live at altitude of 0-500meter-ASL, from parents with secondary education, working fathers with medium category household-income, mothers aged more than 25-35 while fathers were less than 40 years old. Pregnancy history : mothers were 21-34 years old, had less than  2 children, with no comorbidities, trauma, nor folic acid consumption during pregnancy. The majority of CL/P family history was found from the second generation.